Intra-Individual Variability of Human Dental Pulp Stem Cell Features Isolated from the Same Donor - Pilbauerova, Nela; Schmidt, Jan; Soukup, Tomas; Duska, Jan; Suchanek, Jakub (International journal of molecular sciences, 2021)
It is primarily important to define the standard features and factors that affect dental pulp stem cells (DPSCs) for their broader use in tissue engineering. This study aimed to verify whether DPSCs isolated from various teeth extracted from the same donor exhibit intra-individual variability and what the consequences are for their differentiation potential. The heterogeneity determination was based on studying the proliferative capacity, viability, expression of phenotypic markers, and relative length of telomere chromosomes. The study included 14 teeth (6 molars and 8 premolars) from six different individuals ages 12 to 16. We did not observe any significant intra-individual variability in DPSC size, proliferation rate, viability, or relative telomere length change within lineages isolated from different teeth but the same donor. The minor non-significant variances in phenotype were probably mainly because DPSC cell lines comprised heterogeneous groups of undifferentiated cells independent of the donor. The other variances were seen in DPSC lineages isolated from the same donor, but the teeth were in different stages of root development. We also did not observe any changes in the ability of cells to differentiate into mature cell lines-chondrocytes, osteocytes, and adipocytes. This study is the first to analyze the heterogeneity of DPSC dependent on a donor.
Keywords: Adipocytes; Cell Line; zubní dřeň; Chondrocytes; same donor isolation; tukové buňky; individuální biologická variabilita; Cell Differentiation; Tissue Donors; dárci tkání; mladiství; Osteocytes; mužské pohlaví; intra-individual variability; Dental Pulp; regenerative medicine; Cell Proliferation; chondrocyty; stem cell characterization; Cell Lineage; dental stem cells; buněčný rodokmen; ženské pohlaví; Humans; proliferace buněk; Stem Cells; buněčné linie; buněčná diferenciace; Biological Variation, Individual; kmenové buňky; mesenchymal stem cells; Female; Adolescent; osteocyty; lidé; Male